Impact of Intellectual Capital, Profitability and Dividend on Market Capitalization - S. A. Putri; . Azwardi; . Sa’adah (Финансы: теория и практика)
The aim of the study was to find out how strong the impact of intellectual capital, profitability and dividends is on the market capitalization of companies listed on the Indonesia Stock Exchange (IDX) and included in the LQ45 index from 2014 to 2018. The authors employ the multiple linear regression method. They measure the value of intellectual capital by the value added intellectual coefficient (VAIC ™), and the profitability — by return on assets (ROA) and return on equity (ROE). To calculate a dividend per share (DPS), they divide the annual dividend by the number of outstanding shares. The results of this study show that intellectual capital and return on assets (ROA) do not significantly affect the company’s market capitalization, while return on equity (ROE) and dividends do. The authors conclude that by the level of efficiency and effectiveness of the company in capital management, one may see whether investors receive higher profits. Therefore, investors are more interested in companies that have a high level of dividend distribution.